Post-fire concrete edge failure in single and multiple anchors pre-loaded in shear. (June 2021) - Ožbolt, Joško; Lacković, Luka; Tian, Kaipei
Abstract: Concrete edge failure after fire is investigated in this study with the focus on the effect that preloading in shear may have on residual capacity of anchors. Headed stud anchors with single stud, two- and four anchor groups are exposed to the various duration of fire and loaded in shear perpendicular to the free edge of the concrete member up to failure, in both hot and cold state (after cooling) conditions. The influence of the edge distance, embedment depth, number of studs and duration of fire on the load-bearing behavior of anchors are studied. The standard ISO 834 fire curve with fire durations of 15, 30, 60 and 90 min is employed in the simulations. The results of extensive numerical simulations show that anchor behavior is significantly influenced by the fire exposure. Due to the thermally induced damage of concrete the failure pattern, stiffness and load capacity significantly changes. After only 15 min of fire, the reduction of resistance can be more than 50% of the reference resistance. Moreover, the numerical investigations show that the preloading has a relatively strong influence on the residual shear load-bearing capacity of anchors after fire exposure. Highlights: The load-bearing capacity of single anchor and anchor groups in concrete, loaded in shear against free edge of concrete slab, was numerically investigated after fire exposure. Numerical 3D finite element simulations are able to realistically replicate experimental tests. The shear resistance of anchors reduces significantly already after only 15 min of fire exposure. The reduction is stronger for the cold state than for the hot state. Preloading of anchors has significant influence on the residual capacity of anchors after fire exposure.